2012
DOI: 10.1111/nph.12030
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 does not offset greater water stress predicted under climate change for native and exotic riparian plants

Abstract: SummaryIn semiarid western North American riparian ecosystems, increased drought and lower streamflows under climate change may reduce plant growth and recruitment, and favor drought-tolerant exotic species over mesic native species. We tested whether elevated atmospheric CO 2 might ameliorate these effects by improving plant water-use efficiency.We examined the effects of CO 2 and water availability on seedlings of two native (Populus deltoides spp. monilifera, Salix exigua) and three exotic (Elaeagnus angust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 102 publications
6
47
2
1
Order By: Relevance
“…It has been reported that plants grown at eCO 2 may in part compensate the negative effects of drought due to increased water‐use efficiency. Although this has been shown in some studies (Chaudhuri et al ., ; Chaves & Pereira, ; Morgan et al ., ; Manderscheid et al ., ), these interactions were absent in many other studies (Mousseau & Enoch, ; Grünzweig & Körner, ; Derner et al ., ; Vaz et al ., ; Medeiros & Ward, ; Perry et al ., ). In our experiment, CO 2 fertilization compensated for the negative effect of drought on grain yield and water‐use efficiency at maturity, especially in GP (Schmid et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that plants grown at eCO 2 may in part compensate the negative effects of drought due to increased water‐use efficiency. Although this has been shown in some studies (Chaudhuri et al ., ; Chaves & Pereira, ; Morgan et al ., ; Manderscheid et al ., ), these interactions were absent in many other studies (Mousseau & Enoch, ; Grünzweig & Körner, ; Derner et al ., ; Vaz et al ., ; Medeiros & Ward, ; Perry et al ., ). In our experiment, CO 2 fertilization compensated for the negative effect of drought on grain yield and water‐use efficiency at maturity, especially in GP (Schmid et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It is well established that elevated [CO2] leads to reduced stomatal conductance (gs) (Medlyn et al 2001;Wullschleger et al 2002) and could therefore theoretically reduce plant water loss and delay drought-induced mortality by allowing plants to maintain more favourable water status during drought. However, existing studies suggest that plant responses to elevated [CO2] and drought stress are highly variable (Atwell et al 2007;Domec et al 2010;Wertin et al 2010Wertin et al ,2012Ayub et al 2011;Duursma et al 2011;Warren et al 2011;Zeppel et al 2012;Franks et al 2013;Lewis et al 2013;Perry et al 2013). For example,in some studies,elevated [CO2] can partially moderate the impact of drought stress by increasing photosynthesis (Wertin et al 2010;Lewis et al 2013) and carbohydrate reserves (Niinemets 2010;Tissue & Lewis 2010;Ayub et al 2011), thereby providing increased availability of carbon for growth and metabolic activity during mild or moderate drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…We provide evidence that growth under low‐[CO 2 ] conditions could have increased the drought tolerance of some C 3 plants during glacial times compared with the present. Our work also provides mechanistic support for studies indicating that water availability will remain an important factor limiting the productivity of C 3 plants, even as [CO 2 ] increases (Linares et al ., ; Vaz et al ., ; Perry et al ., ). Furthermore, we show that increased productivity at elevated [CO 2 ] may only occur under conditions where higher water use can be accommodated.…”
Section: Discussionmentioning
confidence: 97%